ANALISIS PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR LOGAM DAN SEJENISNYA (Penerapan Model Altman Z-Score yang Telah Dimodifikasi) - Yusika Yerico; Veny Anindya Puspitasari (Jurnal Ekonomika dan Manajemen, 2019)
This study aims to analyze the potential for bankruptcy in ten metal and allied sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2018 period. The data used in this study are secondary data from annual financial statements contained in the Indonesia Stock Exchange (IDX). This study uses the Altman Z-Score model as a tool to measure the potential for bankruptcy of companies that represent financial ratios. The Altman Z-Score formula used is as follows: Z = 0.717X1 + 0.847 X2 + 3.107X3 + 0.420X4 + 0.998X5 with a zone of discrimination, if the Z value is more than 2.9 then the company is in a "healthy" condition, if the value Z is not more than 2.9 and is not smaller than 1.23, the company is in a "gray" condition, and if the Z value is less than 1.23, the company is in a "distress" condition. During the observation period, it was shown that most of the ten companies in the metal and allied sub-sectors listed on the IDX were in gray and distressed conditions. Only 2 out of 10 companies are able to survive and make improvements, namely Beton Jaya Manunggal Tbk, and Lionmesh Prima Tbk.